P440 Comparison of infliximab serum levels between venous and capillary blood in paediatric IBD patients using novel blood sampling technology. (25th January 2019) - Zijlstra, M; Jongsma, M; de Vries, A; Schaap, T; Bloem, K; de Ridder, L
Abstract: Background: Infliximab (IFX) enormously changed the treatment of inflammatory bowel disease (IBD) in paediatric patients over the last years. To optimise IFX treatment outcome, therapeutic drug monitoring is important. Measurements are typically taken by venipuncture. Dried blood sampling (DBS), using capillary blood obtained from a finger prick, may also be used to measure IFX blood levels. For paediatric patients, the latter is less invasive and can be done outside of the hospital, facilitating a more personalised treatment. The aim of this study was to compare IFX blood level measured by venipuncture vs. DBS in paediatric IBD patients. Methods: This prospective clinical pilot study included 20 paediatric IBD patients (aged 6–16 years). Before IFX infusion, blood was collected simultaneously through venipuncture as well as a DBS from a finger prick, using Mitratips© (Neotyrex). The IFX levels were assessed by ELISA (Sanquin, Amsterdam). IFX levels measured in DBS eluates were converted to serum values by making use of a fixed haematocrit value of 0.42. Spearman's correlation coefficient was calculated to examine the correlation between venous IFX serum level and DBS. The Bland–Altman analysis was used to measure limits of agreement. Results: Twenty patients were included, median age 12.1 year [range 8–16 year], two patients with ulcerative colitis, 1 with IBD-Unclassified, and 17 with Crohn's disease. Four patients were excluded from the analysis, since IFX level was below detection level in venepuncture serum and/or DBS. There is significant strong correlation between venous IFX serum levels and DBS ( r = 0.997, p = 0.0001) in the included patients. The mean difference between the two methods is −0.266 (95% CI: −0.592; 0.059) as calculated with Bland–Altman plot. There is no statistical significant difference between venous IFX serum levels and DBS. The limits of agreement are between −1.464 (95% CI: −2.029; −0.900) and 0.932 (95% CI: 0.367; 1.496) (Figure 1). It is worth noting that when using a limited number of patients, as done during this pilot study, the limits of agreement are typically wider. Conclusions: This is the first study comparing venous and capillary infliximab serum levels with novel blood sampling technology in paediatric IBD. There is strong correlation between the methods and acceptable limits of agreement. As such the bloodspot technology could be a good candidate for an alternative method to measure IFX blood levels in paediatric patients and facilitate therapeutic drug monitoring.